2019
DOI: 10.1186/s13045-019-0781-y
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose post-transplant cyclophosphamide and anti-thymocyte globulin as an effective strategy for GVHD prevention in haploidentical patients

Abstract: Background: Low-dose post-transplant cyclophosphamide (PTCy) in conjunction with anti-thymocyte globulin (ATG) appears as a potentially effective graft-versus-host disease (GVHD) prevention strategy in haploidentical hematopoietic cell transplant (haplo-HCT). Our study aims to assess the efficacy of this regimen. Methods:We extended our prospective study in patients treated with low-dose PTCy (14.5 mg/kg on days 3 and 4) in ATG/granulocyte colony-stimulating factor (G-CSF)-based regimen and compared the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
68
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(80 citation statements)
references
References 35 publications
(75 reference statements)
10
68
2
Order By: Relevance
“…Similar results were reported by Bhamidipati et al following a nonmyeloablative preparative regimen (25). More recently, Wang et al showed that the addition of low dose PTCy (14.5 mg/kg on day +3 and +4), to the so-called Beijing protocol, reduced the incidence of grade II-IV aGvHD and improved GvHD-and relapse-free survival (GRFS) (26).…”
Section: Ptcy In Haploidentical Transplantsupporting
confidence: 75%
“…Similar results were reported by Bhamidipati et al following a nonmyeloablative preparative regimen (25). More recently, Wang et al showed that the addition of low dose PTCy (14.5 mg/kg on day +3 and +4), to the so-called Beijing protocol, reduced the incidence of grade II-IV aGvHD and improved GvHD-and relapse-free survival (GRFS) (26).…”
Section: Ptcy In Haploidentical Transplantsupporting
confidence: 75%
“…Patients at high GVHD risk in the HIDT cohort received low-dose corticosteroid prophylaxis [19]. In addition, two doses of 14.5 mg/kg Cy was given on days 3 and 4 after HSCT from maternal donors during the trial period [20].…”
Section: Transplant Protocolmentioning
confidence: 99%
“…Among these strategies, the major one that emerged was to add ATG to PTCY. Several groups have demonstrated that this combination seems to be associated with a lower incidence of acute or chronic GVHD [21][22][23][24][25]. Here, the schedules used present the advantage, similarly to a recent publication [25], of comparing these two prophylaxis regimen (PTCY vs PTCY þ ATG 2.5 mg/kg, both with cyclosporine and mycophenolate mofetil) in a large cohort of patients.…”
Section: Discussionmentioning
confidence: 76%